CHEST X-RAY IN HUMAN IMMUNODEFICIENCY VIRUS (HIV) INFECTED-PEDIATRICS: A CASE SERIES REVIEW - Dhira Rizki Putri; Marichatul Jannah (Poltekkes Kemenkes Semarang, 2022)
In 2017, Indonesia had 4.950 new cases of HIV infection in pediatrics. In HIV, a chest x-ray is generally used to determine the Opportunistic Infections (OIs) to accelerate treatment. There are differences in the projections and the typical features on chest x-ray in each OI. The research aims to study the projections and the role of pediatric chest x-ray examination in HIV. This is a descriptive qualitative research design with a case series. In this series, 5 pediatric patients with HIV infection are described with tuberculosis, pneumonia, and bronchiectasis. A chest x-ray in pediatrics is the most accessible investigation for respiratory disease and has an important role in the initial assessment and the follow-up of respiratory disease in HIV-infected children. It is recommended that a pediatric chest x-ray should be carried out with PA projection to obtain more optimal results. Pediatrics with clinical HIV infection can employ chest x-rays to find typical features of bilateral hilar adenopathy in cases of TB, focal and multifocal parenchymal abnormalities in cases of pneumonia, or dilated and thickened airways that appear as ring shadows or tramways in bronchiectasis.